Menerapkan Metode Outentic Learnign Untuk Meningkatkan Motivasi dan Hasil Belajar IPA - Anidar Anidar (JURNAL GLOBAL EDUKASI, 2021)
Abstract: Classroom action research in general aims to improve the quality of learning for fifth grade students of SDN 010006 Sei Apung by applying the Outentic Learning learning method on science subjects with the material of Human and Animal Organs. The classroom action research was carried out in class V SDN 010006 Sei Apung, totaling 25 students. The subjects of this study were fifth grade science students and fifth grade students of SDN 010006 Sei Apung. Data were collected through observation, interviews, tests, and study documentation. The results of the comparison of teacher research observations in the first cycle were 14.3% while the second cycle was 24.3%. The results of the learning process before the study applied the Outentic Learning method to increase motivation and learning outcomes for the subject matter of Human Bodies and Animals in Science Lessons for Class V Students of SDN 010006 Sei Apung kec. Tanjung Balai TP. 2019/2020 achieved an average score of 60.3%. After the motivation, the research was carried out through the first cycle and the second cycle of reflection and the recommended average value reached 84.6%, meaning that there was an increase of 24.3%. Keywords: animal; human; organs; outentic learning.  Abstrak: Penelitian tindakan kelas secara umum bertujuan untuk meningkatkan kualitas pembelajaran untuk peserta didik kelas V SDN 010006 Sei Apung dengan menerapkan metode pembelajaran Outentic Learning pada mata pelajaran IPA dengan materi Organ Tubuh Manusia dan Hewan. Penelitian tindakan kelas dilaksanakan dikelas V SDN 010006 Sei Apung yang berjumlah 25 orang siswa. Subjek penelitian ini adalah siswa IPA kelas V dan siswa kelas V SDN 010006 Sei Apung, data dikumpulkan melalui observasi, wawancara, test, dan study dokumentasi. Hasil perbandingan observasi penelitian guru pada siklus I adalah sebesar 14.3 % sedangkan siklus II sebesar 24.3 % Hasil proses belajar sebelum penelitian menerapkan metode Outentic Learning untuk meningkatkan motivasi dan hasil belajar materi Organ Tubuh Manusia dan Hewan Pelajaran IPA Siswa Kelas V SDN 010006 Sei Apung kec. Tanjung Balai TP. 2019/2020 mencapai nilai rata-rata 60.3%. setelah termo-tivasi dilakukan penelitian melalui siklus I dan siklus II refleksi dan rekomendasi nilai rata-rata mencapai 84.6% berarti ada peningkatan sebesar 24.3%.            Kata Kunci: hewan; manusia; organ tubuh; outentic learning.